TBX2 controls a proproliferative gene expression program in melanoma - Lu, Sizhu; Louphrasitthiphol, Pakavarin; Goradia, Nishit; Lambert, Jean-Philippe; Schmidt, Johannes; Chauhan, Jagat; Rughani, Milap G; Larue, Lionel; Wilmanns, Matthias; Goding, Colin R (Genes & development, 2021)
Senescence shapes embryonic development, plays a key role in aging, and is a critical barrier to cancer initiation, yet how senescence is regulated remains incompletely understood. TBX2 is an antisenescence T-box family transcription repressor implicated in embryonic development and cancer. However, the repertoire of TBX2 target genes, its cooperating partners, and how TBX2 promotes proliferation and senescence bypass are poorly understood. Here, using melanoma as a model, we show that TBX2 lies downstream from PI3K signaling and that TBX2 binds and is required for expression of E2F1, a key antisenescence cell cycle regulator. Remarkably, TBX2 binding in vivo is associated with CACGTG E-boxes, present in genes down-regulated by TBX2 depletion, more frequently than the consensus T-element DNA binding motif that is restricted to Tbx2 repressed genes. TBX2 is revealed to interact with a wide range of transcription factors and cofactors, including key components of the BCOR/PRC1.1 complex that are recruited by TBX2 to the locus. Our results provide key insights into how PI3K signaling modulates TBX2 function in cancer to drive proliferation.